Preliminary Report on the Earthenware Pottery from Ille Cave and Rockshelter, Palawan, Philippines - Balbaligo, Yvette (Hukay; Vol 15 (2010))
Between 2004 and 2008, approximately 12,600 earthenware pottery sherds were excavated at Ille Cave and Rockshelter, a multi ‐ period burial and occupation site and one of several cave complexes in El Nido, Palawan, and the Philippines. The report presents the results from the first systematic analysis of the pottery. It gives details of pottery quantities, describes fabric and form, and discusses manufacture and decoration styles.